PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL DALAM MENINGKATKAN DAYA TARIK BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA KELAS 4 DI SD NEGERISUKARATU 6 - Ranita Aurike; Selfa Indi Nursyamsiah; Desty Endrawati Subroto (CV. Denasya Smart Publisher, 2024)
This research is motivated by the lack of use of technology-based learning media in Indonesia mathematics learning for grade IV students at SD Negeri SUKARATU 6. Student learning activities seem monotonous so that students are less enthusiastic about learning mathematics. This research aims to analyze usage wordwall game learning media on students' interest in learning mathematics. This research uses a qualitative descriptive research method. This research was carried out in class IV of SD Negeri Sukaratu 6, totaling 30 students as research subjects for mathematics subjects. The data collection techniques used were observation and interviews. The results of the research prove that the wordwall learning media is an interactive media that is easy to use in the learning activities of grade IV students at SD Negri Sukaratu 6. So, it can be concluded that the wordwall learning media can increase students' interest in learning mathematics.